Impact of initial chemotherapy regimen on outcomes for patients with double‐expressor lymphoma: A multi‐center analysis. Issue 4 (4th August 2021) - D'Angelo, Christopher R.; Hanel, Walter; Chen, Yi; Yu, Menggang; Yang, David; Guo, Ling; Karmali, Reem; Burkart, Madelyn; Ciccosanti, Colleen; David, Kevin; Risch, Zachary; Murga‐Zamalloa, Carlos; et al.
Abstract: Diffuse large B‐cell lymphoma featuring overexpression of MYC and B‐Cell Lymphoma 2 (double expressor lymphoma, DEL) is associated with poor outcomes. Existing evidence suggesting improved outcomes for DEL with the use of more intensive regimens than R‐CHOP is restricted to younger patients and based on limited evidence from low patient numbers. We retrospectively evaluated the impact of intensive frontline regimens versus R‐CHOP in a multicenter analysis across 7 academic medical centers in the United States. We collected 90 cases of DEL, 46 out of 90 patients (51%) received R‐CHOP and 44/90 (49%) received an intensive regimen, which was predominantly DA‐EPOCH‐R. Treatment cohorts were evenly balanced for demographics and disease characteristics, though the intensive group had a higher lactate dehydrogenase (LDH, 326 vs. 230 U/L p = 0.06) and presence of B‐symptoms (50% vs. 22%, p = 0.01) compared to the R‐CHOP cohort. There was no difference in PFS (median 53 vs. 38 months, p = 0.49) or overall survival (67 vs. not reached months, p = 0.14) between the R‐CHOP and intensive therapy cohorts, respectively. On multivariate analysis, intensive therapy was associated with a hazard ratio of 2.35 (95% CI 0.74–7.41), though this was not statistically significant. Additionally, a subgroup analysis of intermediate high‐risk lymphoma defined by IPI ≥3 did not identify a difference in survival outcomes between regimens. We conclude that in our multi‐center cohort there is no evidence supporting the use of intensive regimens over R‐CHOP, suggesting that R‐CHOP remains the standard of care for treating DEL.